Acquired long QT syndrome in a patient with human immunodeficiencyvirus and disseminated Mycobacterium avium complex - Singh, Bhupinder; Saini, Rakshit Singh; Gupta, Ira; Verma, Sakshi (Indian Journal of Case Reports, 2026)
Acquired long QT syndrome is usually seen secondary to metabolic abnormalities and medications, including macrolide antibiotics, anti-psychotics, and anti-arrhythmics. QT prolongation has also been seen in patients with human immunodeficiency virus (HIV), particularly those with poorly controlled HIV status, immunocompromised state, and electrolyte imbalances associated with chronic HIV infection. We present a case report of a young male with poorly controlled HIV (CD4 count 11 cells/uL, high viral load) who presented with fatigue, shortness of breath, and a mechanical fall, with an initial electrocardiogram showing a prolonged corrected QT (QTc) interval, and was eventually found to have disseminated Mycobacterium avium complex (MAC) infection upon bone marrow biopsy. The primary clinical dilemma involved starting initial macrolide-based antibiotic therapy for disseminated MAC, and in the presence of a QTc >500. The case highlights the complex challenge of managing critical illness in advanced HIV and balancing the pro-arrhythmic danger of treatment against the immediate mortality of untreated infection when widespread MAC necessitates the use of macrolides.